Factors Affecting Growth of Tengmalm's Owl (Aegolius funereus) Nestlings: Prey Abundance, Sex and Hatching Order - Zárybnická, Markéta; Riegert, Jan; Brejšková, Lucie; Šindelář, Jiří; Kouba, Marek; Hanel, Jan; Popelková, Alena; Menclová, Petra; Tomášek, Václav; Šťastný, Karel (PloS one, 2015)
In altricial birds, energy supply during growth is a major predictor of the physical condition and survival prospects of fledglings. A number of experimental studies have shown that nestling body mass and wing length can vary with particular extrinsic factors, but between-year observational data on this topic are scarce. Based on a seven-year observational study in a central European Tengmalm's owl population we examine the effect of year, brood size, hatching order, and sex on nestling body mass and wing length, as well as the effect of prey abundance on parameters of growth curve. We found that nestling body mass varied among years, and parameters of growth curve, i.e. growth rate and inflection point in particular, increased with increasing abundance of the owl's main prey (Apodemus mice, Microtus voles), and pooled prey abundance (Apodemus mice, Microtus voles, and Sorex shrews). Furthermore, nestling body mass varied with hatching order and between sexes being larger for females and for the first-hatched brood mates. Brood size had no effect on nestling body mass. Simultaneously, we found no effect of year, brood size, hatching order, or sex on the wing length of nestlings. Our findings suggest that in this temperate owl population, nestling body mass is more sensitive to prey abundance than is wing length. The latter is probably more limited by the physiology of the species.
Keywords: Wings, Animal; Male; Biological Phenomena; hnízdění; Nesting Behavior; Strigiformes; Reproduction; Physiological Phenomena; fyziologické jevy; křídla zvířecí; mužské pohlaví; biologické jevy; rozmnožování; Stringiformes; Animals; ženské pohlaví; zvířata; Sexual Behavior; sexuální chování; Arvicolinae; myši; Mice; Female